Research Methodology - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (Springer, 2016)
This chapter discussed the methodological part of the research. This is essential in investigating the research hypotheses developed. This is a quantitative research which utilizes a cross-sectional survey to collect the primary data required for this study. The following Chap. 5 was written to report on data analyses and research findings accordingly to the stated research hypotheses as contended in the present study.